Deflection Measurement System in Flexible Bars Using Eulerian Video Magnification (EVM) Method - Rayyan, Muhammad (Journal of Engineering and Science, 2024)
Deflection testing plays a pivotal role in assessing a material’s elasticity, which directly influences the safety and operational reliability of engineering structures. This study develops and evaluates a deflection measurement system employing a flexible bar test apparatus, integrating the Eulerian Video Magnification (EVM) technique. EVM enhances imperceptible displacements and motion changes in recorded video, enabling precise deflection observation. Experimental results indicate that EVM-based measurements recorded a peak deflection of 4.6693 mm and a minimum of −4.78208 mm, while accelerometer measurements yielded a peak of 3.7646 mm and a minimum of −3.7685 mm at 3,600 RPM. The results confirm that deflection magnitude increases proportionally with motor speed, aligning with prior research findings. These outcomes demonstrate the viability of EVM as a non-contact, effective method for detecting small-scale motion variations in materials that are difficult to monitor using conventional approaches. The proposed system improves the accuracy and efficiency of deflection measurements, offering significant implications for structural design and engineering analysis.